2021
DOI: 10.1186/s12896-020-00658-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing various protocols of human and bovine ovarian tissue decellularization to prepare extracellular matrix-alginate scaffold for better follicle development in vitro

Abstract: Background Nowadays, the number of cancer survivors is significantly increasing as a result of efficient chemo/radio therapeutic treatments. Female cancer survivors may suffer from decreased fertility. In this regard, different fertility preservation techniques were developed. Artificial ovary is one of these methods suggested by several scientific groups. Decellularized ovarian cortex has been introduced as a scaffold in the field of human fertility preservation. This study was carried out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…A handful of studies have shown high biocompatibility with ovarian cell types grown in reconstituted dECM hydrogels and scaffolds. A mixture of sodium alginate with decellularized murine ovarian tissue supported in vitro follicle survival ( Nikniaz et al, 2021 ). Preliminary studies of hydrogels derived from decellularized porcine ovarian ECM highlighted the effect of ECM stiffness on ovarian follicle development, with stiffer matrices reducing oocyte viability and triggering premature follicle release ( Buckenmeyer et al, 2016 ), though this effect has not been investigated with ovarian cancer cells.…”
Section: 3d In Vitro Ovarian Cancer Modelsmentioning
confidence: 99%
“…A handful of studies have shown high biocompatibility with ovarian cell types grown in reconstituted dECM hydrogels and scaffolds. A mixture of sodium alginate with decellularized murine ovarian tissue supported in vitro follicle survival ( Nikniaz et al, 2021 ). Preliminary studies of hydrogels derived from decellularized porcine ovarian ECM highlighted the effect of ECM stiffness on ovarian follicle development, with stiffer matrices reducing oocyte viability and triggering premature follicle release ( Buckenmeyer et al, 2016 ), though this effect has not been investigated with ovarian cancer cells.…”
Section: 3d In Vitro Ovarian Cancer Modelsmentioning
confidence: 99%
“…Alginate hydrogel Nikniaz et al (2021) cultured ovarian follicles in decellularized ovarian scaffold using alginate hydrogel, examined follicle survival and examined the different decellularization protocols to compare optimized tissue degradation biocompatibility and DNA residues. In this study, the ECM scaffold matrix does not show a significant difference in the decellularized structure of the scaffold; however, the method for remaining DNA elimination is different, and cell viability can be affected by different decellularization methods (Berkholtz et al, 2006).…”
Section: Whole-ovary Decellularization Methodsmentioning
confidence: 99%
“…The results of this study are interpreted according to the following issues: (a) This study was performed in laboratory conditions for 7 days and needed further studies, (b) Decellularization of the ovarian cortex by SDS‐Triton‐Ammonium has less residual DNA than other methods and is also suitable for follicle culture, (c) Preantral follicles in combination with ECM and alginate survive and grow. (d) Preantral follicles survive and grow with ECM and alginate (Nikniaz et al., 2021).…”
Section: In Vitro Scaffolds Usementioning
confidence: 99%
“…ECM products that are obtained from decellularization of female reproductive organs have salient roles in the field of reproductive medicine, with research focusing mainly on those that are derived from the uterus [ 51 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ], ovary [ 50 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], cervix [ 93 ], vagina [ 94 , 95 ], and placenta [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. The variable methods that are used for decellularization are dependent on the tissue type and its characteristics.…”
Section: Deriving Ecm Hydrogels From Reproductive Organsmentioning
confidence: 99%